The Influence of Industrial Policy on Innovation in Startup Enterprises: An Empirical Study Based on China's GEM Listed Companies. (29th October 2021) - Wang, Fang; Zhu, Deyong
Abstract : This study uses China's Growth Enterprises Market (GEM) listed companies from 2011 to 2017 as samples to examine the impact of industrial policies on innovation in startups from three dimensions, namely, selective industrial policies, government subsidies, and financial support. The results show that selective industrial policies have no effect on the innovation output of startups. Financial support can significantly promote the innovation output of entrepreneurial enterprises; structural differences exist in the impact of government subsidies on the innovation of entrepreneurial enterprises. The influence of industrial policy on the innovation of entrepreneurial enterprises depends on the research and development intensity of enterprises, the level of regional economic development, the leadership structure of enterprises, and other factors. This study's findings have significant practical significance for the implementation of a national innovation-driven development strategy and to guide industrial policies that better promote enterprise innovation.